2020
DOI: 10.1111/exd.14245
|View full text |Cite
|
Sign up to set email alerts
|

Re‐innervation of human skin by rat dorsal root ganglia permits to study interactions between sensory nerve fibres and native human dermal mast cells ex vivo

Abstract: Re-innervation of human skin by rat dorsal root ganglia permits to study interactions between sensory nerve fibres and native human dermal mast cells ex vivo While the study of full-thickness human skin organ culture (hSOC) has many advantages over so-called 3D skin "equivalents" in terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Yet, 3D cultures of the same primary skin cells 49 are still far more complex than their monolayer counterparts. For instance, a recent genome-wide methylation study showed no correlation between methylation status and transcriptome changes during keratinocyte differentiation in a monolayer culture, 22 despite other data showing significant methylation changes during in vivo skin morphogenesis.…”
Section: What Org Anot Ypi C Culture S C An and C An ' T Domentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, 3D cultures of the same primary skin cells 49 are still far more complex than their monolayer counterparts. For instance, a recent genome-wide methylation study showed no correlation between methylation status and transcriptome changes during keratinocyte differentiation in a monolayer culture, 22 despite other data showing significant methylation changes during in vivo skin morphogenesis.…”
Section: What Org Anot Ypi C Culture S C An and C An ' T Domentioning
confidence: 99%
“…Critically, 3D cultures, no matter how sophisticated, lack system‐level aspects of normal skin, such as fully functioning vasculature, immune system and innervation. Even though this may be partially compensated for with ex vivo ‐reinnervation protocols, 48 this puts limits on the maximum size that 3D cultures can achieve before experiencing hypoxia and simplifies their responses to external and neurotrophic stimuli.…”
Section: What Organotypic Cultures Can and Can't Domentioning
confidence: 99%
See 1 more Smart Citation